2019
DOI: 10.1111/1365-2656.13007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for locally adaptive metabolic rates among ant populations along an elevational gradient

Abstract: As global temperatures rise, the mechanistic links between temperature, physiology and behaviour will increasingly define predictions of ecological change. However, for many taxa, we currently lack consensus about how thermal performance traits vary within and across populations, and whether and how locally adaptive trait plasticity can buffer warming effects. The metabolic cold adaptation hypothesis posits that cold environments (e.g. high elevations and latitudes) select for high metabolic rates (MR), even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 63 publications
4
31
1
Order By: Relevance
“…Furthermore, Dahlhoff et al (2019) showed that development was slower at higher elevations in the leaf beetle Chrysomela aeneicollis because of a reduction in metabolic rate. That said, in A. iberica, the opposite was observed along the same study gradient as ours: Shik, Arnan, Oms, Cerdá, and Boulay (2019) discovered that the metabolic rates of ants from higher elevations increased faster at low temperatures but that the temperature at which metabolic rates levelled out was the same across populations. They also observed that body size (mg of dry mass) was significantly larger for higher elevation ants than for lower elevation ants.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, Dahlhoff et al (2019) showed that development was slower at higher elevations in the leaf beetle Chrysomela aeneicollis because of a reduction in metabolic rate. That said, in A. iberica, the opposite was observed along the same study gradient as ours: Shik, Arnan, Oms, Cerdá, and Boulay (2019) discovered that the metabolic rates of ants from higher elevations increased faster at low temperatures but that the temperature at which metabolic rates levelled out was the same across populations. They also observed that body size (mg of dry mass) was significantly larger for higher elevation ants than for lower elevation ants.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies instead focused either on intraspecific clines for a small number of species, interspecific clines or community-wide clines. At the intraspecific level, previous work shows that ants increase in size with increasing latitude (Heinze et al, 2003) and elevations (Bernadou, Römermann, Gratiashvili, & Heinze, 2016;Purcell, Pirogan, Avril, Bouyarden, & Chapuisat, 2016;Shik, Arnan, Oms, Cerdá, & Boulay, 2019), consistent with the hypothesis that lower temperatures lead to larger body size.…”
Section: Introductionsupporting
confidence: 81%
“…Taking into account seasonal variation, social organisation, and life‐history traits, it showed that variation in body size was generally consistent with Bergmann's rule. In ants, Aphaenogaster iberica workers have been found to be larger at higher latitudes (Shik et al ., 2019). Furthermore, in a number of social insect species, researchers have observed a positive relationship between body size and heat tolerance, where larger workers were more heat resistant than smaller workers [ants (Cerdá & Retana, 1997, Cerdá & Retana, 2000, Clémencet et al ., 2010, Oberg, del Toro, & Pelini, 2012, Baudier et al ., 2015, Baudier & O'Donnell, 2016, 2017, Wendt & Verble‐Pearson, 2016); termites (Janowiecki et al ., 2019)].…”
Section: Morphological Adaptationsmentioning
confidence: 99%
“…In honeybee ( Apis mellifera ) populations adapted to colder climates, major energy‐producing mitochondrial pathways were found to be upregulated (Parker et al ., 2010). In both ants ( Aphaenogaster iberica ; Shik et al ., 2019) and wasps ( Polistes dominula , Kovac et al ., 2017), workers from populations found at higher altitudes had higher metabolic rates than did workers from populations found at lower altitudes.…”
Section: Physiological and Molecular Adaptationsmentioning
confidence: 99%